0,75 + x = 1/4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
1) 2,75 - 5/6 × 2/5 = 2,75 - (5/6) × (2/5) = 2,75 - 1/3 = 2,75 - 0,33 = 2,42
2) 1,25 - (5/6 - 0,75) - 3/5 = 1,25 - (5/6 - 0,75) - 3/5 = 1,25 - (5/6 - 3/4) - 3/5 = 1,25 - (5/6 - 9/12) - 3/5 = 1,25 - (10/12 - 9/12) - 3/5 = 1,25 - 1/12 - 3/5 = 1,25 - 0,08 - 0,6 = 1,25 - 0,68 = 0,57
3) 4/9 × 0,75 + 8/5 + 3,125 = (4/9) × 0,75 + 8/5 + 3,125 = 0,44 + 8/5 + 3,125 = 0,44 + 1,6 + 3,125 = 0,44 + 4,725 = 5,165
4) 1,125 - 4/7 - 0,12 = 1,125 - (4/7) - 0,12 = 1,125 - 0,57 - 0,12 = 0,435 - 0,12 = 0,315
5) (1/3 + 0,4) × 3,5 + (1/6 + 0,75) × 6/5
![](https://rs.olm.vn/images/avt/0.png?1311)
= 0,75 x 0,25 + 0,75 x 1,25 - 0,75 x 0,5
= 0,75 x ( 0,25 + 1,25 - 0,5 )
= 0,75 x 1
= 0,75
![](https://rs.olm.vn/images/avt/0.png?1311)
=3/4.0,25+3/4.1,25-3/4.0,5
=3/4.(0,25+1,25-0,5)
=3/4.10
=15/2
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(0,75\times26+49\times\frac{3}{4}+\frac{3}{4}\times24+\) \(0,75\)
\(=\) \(0,75\times\left(26+1\right)+\frac{3}{4}\times\left(49+24\right)\)
\(=\) \(\frac{3}{4}\times27+\frac{3}{4}\times73\)
\(=\) \(\frac{3}{4}\times\left(27+73\right)\)
\(=\)\(\frac{3}{4}\times100=75\)
b) câu b,c làm tương tự
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(\left|x\right|+0,75=2\Rightarrow\left|x\right|=1,25\Rightarrow x=\pm1,25\)
b, \(\left|x+\dfrac{1}{3}\right|-4=1\Rightarrow\left|x+\dfrac{1}{3}\right|=5\Rightarrow\left|x\right|=\dfrac{14}{3}\Rightarrow x=\pm\dfrac{14}{3}\)
c,
\(\left|x\right|+2,5=0\Rightarrow\left|x\right|=-0,25\) (vô lí)
Vì \(\left|x\right|\ge0\) => x vô nghiệm
a) \(\left|x\right|+0,75=2\)
\(\Leftrightarrow\left|x\right|=2-0,75=1,25\)
\(\Rightarrow\left[{}\begin{matrix}x=-1,25\\x=1,25\end{matrix}\right.\)
b) \(\left|x+\dfrac{1}{3}\right|-4=1\)
\(\Leftrightarrow\left|x+\dfrac{1}{3}\right|=1+4=5\)
\(\Leftrightarrow\left[{}\begin{matrix}x+\dfrac{1}{3}=5\\x+\dfrac{1}{3}=-5\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{14}{3}\\x=-\dfrac{16}{3}\end{matrix}\right.\)
c) \(\left|x\right|+2,5=0\)
\(\Leftrightarrow\left|x\right|=0-2,5=-2,5\)
Vì \(\left|x\right|\ge0\) mà \(-2,5< 0\) nên \(x\in\varnothing\)
\(0,75+x=\frac{1}{4}\)
\(\frac{3}{4}+x=\frac{1}{4}\)
\(\Rightarrow x=\frac{1}{4}-\frac{3}{4}=-\frac{1}{2}\)